2010
DOI: 10.1108/13522751011053617
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in researching consumer ethics: a methodological experiment

Abstract: Practical implications -There is a need for academics and marketing researchers to adopt innovative observational research methods to investigate ethical consumer behaviour.Originality/value -Provides a reflection on a unique, emergent approach to researching ethical consumer behaviour. The findings of the research will be of value to anyone researching consumer ethics or buyer behaviour in retail, grounded theorists or those interested in qualitative interactive research techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Given the research objective, an introspective qualitative approach (i.e., the examination of one's own conscious thoughts) was deemed appropriate for this study (Hiller, 2010).…”
Section: Overviewmentioning
confidence: 99%
“…Given the research objective, an introspective qualitative approach (i.e., the examination of one's own conscious thoughts) was deemed appropriate for this study (Hiller, 2010).…”
Section: Overviewmentioning
confidence: 99%
“…This study is of course not without its limitations, not least the potential for a social desirability or method bias to which all studies of self-reported behavior are subject (see e.g., [52]). A social desirability bias would lead to an over-or underestimation of behavior for all categories, while consumer inability to accurately recall actions in the given time period on a general abstract level would produce different accountings of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable consumption refers to consumption that supports the ability of current and future generations to meet their material and other needs, without causing irreversible damage to the environment or loss of function in natural systems. In a related vein, sustainable consumption also can be described as an aspect of consumer behaviour that involves pre-purchase, purchase and post-purchase components [32,27]. In line of reasoning, the reviewer considered the previous journal articles that use sustainable purchase intention, willingness to pay and purchasing behaviour as independent variables.…”
Section: Sustainable Consumptionmentioning
confidence: 99%